Answer:
(x−2)^3=x^3−6x^2+12x-8
Step-by-step explanation:
if you are talking about the binomial (x−2)^3 you must expand then simplify. (x-2)3 you would just remove the parenthesizes and multiply -2 with 3 to get x-6 but I think you meant (x-2)^3
Too lazy to format so here
R = 20D =
R = 20(6) =
120 = 20(6)
r = 120 = the days it cost to rent bike
so expensive
Initial(1-markdown)
387.50(1-49%)=197.625
final answer: $197.63
Answer:
45
Step-by-step explanation:
45 > 42 but < 47 and it's a multiple of 3 and 5
The zeros are 5/2 and -4/5, I think.